Exploration of Interior Material Based on Plastic Waste - Dheana Wibowo; Yully Ekawardhani (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research is to determine the exploration of interior materials made from plastic waste, such as the process of collecting materials and the stages until they can become interior materials. To find out the process and stages, this research uses data collection methods in the form of observation, interviews, and documentation. The findings of this research are the analysis of plastic waste such as the content and properties of plastic when used as an exploration of interior materials and the strength of the interior material itself. Plastic is not only dangerous for humans, but also endangers all living things and the environment around us, especially according to Indonesian domestic statistics, Indonesia is a country that ranks second in the largest contributor of plastic waste. Based on data analysis, it can be concluded that the formation of knowledge regarding the creation of creative products to tackle plastic waste, by using it as an interior material is able to turn useless objects into very useful object for the survival of human life.